The Role of Assertive Communication in Managing Internal Conflicts Among Members of the Indonesian Islamic Student Movement (PMII) - Ikah Marikah; Siti Khumayah; Aghnia Dian Lestari (Greenation Publisher & Yayasan Global Resarch National, 2026)
Differences in the orientations and backgrounds of student organization members have the potential to give rise to internal conflicts that can hinder the organization’s effectiveness if not managed properly. This study aims to analyze the practices and role of assertive communication in managing internal conflicts, as well as its contribution to solidarity and organizational sustainability among m embers of the PMII Green Campus Indramayu Branch. The study employs a descriptive qualitative approach through semi-structured in-depth interviews, participatory observation, and document analysis, utilizing the Miles and Huberman model. The findings indicate that assertive communication is implemented through the argumentative expression of opinions, decision-making based on collective deliberation, and the proportional management of emotions. Assertive communication plays a central role in conflict resolution through an integrative approach that accommodates the interests of all parties, while simultaneously strengthening members’ cohesion and sense of belonging to the organization. This study concludes that assertive communication is a strategic competency that functions as an integrative mechanism in maintaining the stability and sustainability of student organizations based on Islamic values.